Discontinuity As Catastrophic Event in Urban Design - Sana Sati Abbas; Baya Belmessaud Belmessaud (Iraqi Journal of Architecture and Planning, 2009)
This research is an attempt to study the discontinuity as a catastrophic eventin Urban Design, where this phenomenon had been studied in many displines such asMathematics, Planning , lv{edicine ,Surgery and Biology.The research studied this phenomenon from linguistics and conceptual pointsof views, and submitted its basics in Mathematics according to the Theory ofCatasffophe. The research try to borrow this Theory from this field and built aProgramme to measure and explore the Discontinuity as a Catastrophic Event inUrban Design.The case study was Thefabric surrounded by a new oneCasaba of Algeria , rafuch is a traditional urbanThe research had prepared the axial maps of the Casaba of Algeria for theyears (1830,1846,1880,1996,2001), and studied the Relative asymmetry,which wasconsidered as a Behavioral variable affected by two Control variables rvhich were theConnectivity and the Local Control.The research found that there was Bimodality in the behavior of thetraditional urban fabric where the Trajectory of balance Manifold moved fromsegregation to integration by the effect of the new fabric.The research also found that there were two Catastrophic Events happened inthe traditional fabric at the years (1830 and 1880) , as a result oflhe unstability of thesystem ,there types were a Cusp Catastrophe.The Theory of Catastrophe add a new items to the Urban Design such asSingularity, Unstability , and Conflict Nuclei, where the research had proved theirappearance in the traditional urban fabric by the effect ofthe new oneThis research stands as a pioneering attempt in this field.